Report on the International Society for Laboratory Hematology Survey on guidelines to support clinical hematology laboratory practice. (9th May 2016) - Hayward, C. P. M.; Moffat, K. A.; George, T. I.; Proytcheva, M.; Iorio, A.
Summary: Introduction: Given the importance of evidence‐based guidelines in health care, we surveyed the laboratory hematology community to determine their opinions on guideline development and their experience and interest in developing clinical hematology laboratory practice guidelines. Methods: The study was conducted using an online survey, distributed to members of the International Society for Laboratory Hematology (ISLH) in 2015, with analysis of collected, anonymized responses. Results: A total of 245 individuals participated. Most worked in clinical and/or research laboratories (83%) or industry (11%). 42% felt there were gaps in current guidelines. The majority (58%) recommended that ISLH engages its membership in guideline development. Participants differed in their familiarity with, and use of, different organizations' guidelines. Participants felt it was important to follow best practice recommendations on guideline development, including engagement of experts, statement about conflict of interests and how they were managed, systematic review and grading evidence for recommendations, identifying recommendations lacking evidence or consensus, and public input and peer review of the guideline. Moreover, it was considered important to provide guidelines free of charge. Industry involvement in guidelines was considered less important. Conclusions: The clinical laboratory hematology community has high expectations of laboratory practice guidelines that are consistent with recent recommendations on evidence‐based guideline development.